Therapy and prognosis of subdural collections - Renda, Yavuz; Öztek, Z.; Hasan, Enver (The Turkish Journal of Pediatrics, 1972)
65 cases with subdural collections were studied regarding etiology, type of treatment and prognosis. Those treated medically were compared with surgically treated cases and better prognosis was seen in the medically treated post-infectious cases. Surgical treatment was found necessary only in cases which developed intracranial pressure.